Simulating of snow cover formation by the model of interaction between the land surface and the atmosphere (SWAP) - E. M. Gusev; O. N. Nasonova (Лëд и снег)
In framework of the project «The Earth system Models – Snow Models Intercomparison Project» (ESMSnowMIP), calculations of snow storages were carried out on ten experimental sites organized for longterm monitoring of the snow cover variability in various regions of the globe. The calculation method is based on the physical and mathematical description of heat and moisture exchange processes occurring within the system «ground water – soil – vegetation cover/snow cover – surface layer of the atmosphere», and it is implemented in the form of the model of interaction between the land surface and the atmosphere (SWAP). The model was developed at the Institute of water problems (IWP) of Russian Academy of Sciences. The model makes possible to calculate components of water and heat balances and different characteristics of the hydrological regime of terrestrial ecosystems and river basins having different spatial scales and located in different natural conditions. Good quality of reproduction of the snow storages variability on all considered sites is reached that allows consideration of the SWAP model as one of the best models of the snow cover formation. Thus, the SWAP model has a sufficiently optimal degree of complexity of the algorithm for reproducing the dynamics of snow cover, which is necessary and sufficient in global and regional hydrological models describing formation of the water balance of the land in the cold regions of the planet, and can be used to create scenario forecasts of snow dynamics (as the important part of the cryosphere). This conclusion is verified by the results of using the SWAP model to reproduce long-term variability of snow storages in basins of the River Lena and the River Ob (with its tributary Irtysh) which are the two largest rivers of the Russian Federation. The calculated and measured characteristics of snow cover dynamics for these basins are shown to be in good agreement.